Durability of Supplemental Nucleus Pulposus Allograft in Patients with Lumbar Discogenic Pain - Costandi S; Beall DP; Davis TT; Amirdelfan K; Naidu RK; DePalma MJ; Yoon ES; Fleming JW; Block JE; Mekhail N (Journal of Pain Research)
Shrif Costandi,1 Douglas P Beall,2 Timothy T Davis,3 Kasra Amirdelfan,4 Ramana K Naidu,5 Michael J DePalma,6 Edward S Yoon,7 Jacob W Fleming,8 Jon E Block,9 Nagy Mekhail1 1Pain Management, Cleveland Clinic, Cleveland, OH, USA; 2Comprehensive Specialty Care, Edmond, OK, USA; 3Source Healthcare, Santa Monica, CA, USA; 4Boomerang Healthcare, Inc., Walnut Creek, CA, USA; 5MarinHealth Spine Institute, Larkspur, CA, USA; 6Virginia iSpine Physicians, Richmond, VA, USA; 7Interventional Radiology, Hospital for Special Surgery, New York, NY, USA; 8Vascular and Interventional Specialists, Dallas, TX, USA; 9Private Practice, San Francisco, CA, USACorrespondence: Jon E Block, Private Practice, 2210 Jackson Street, Ste. 401, San Francisco, CA, 94115, USA, Tel +1 415-775-7947, Email jb@drjonblock.comBackground: The objective of this study was to determine the degree of improvement in lumbar discogenic pain severity and associated back impairment in patients with chronic axial low back pain treated with intradiscally delivered allogeneic nucleus pulposus (NP) at up to two vertebral levels (L1-S1).Methods: Prospective, single-arm clinical study conducted at 6 sites in the US involving 28 participants with discogenic pain (mean age: 44 ± 13 yrs) and modified Pfirrmann grade 3– 7 on magnetic resonance imaging. This report includes the final participant follow up at 24 months post procedure. Back pain severity was evaluated using an 11-point numeric rating scale (NRS) and back function using the Oswestry Disability Index (ODI). Minimal clinically important difference (MCID) and substantial clinical benefit (SCB) were set at ≥ 30% and ≥ 50% over baseline, respectively. The patient acceptable symptom state (PASS) threshold for pain severity was ≤ 3.Results: The average improvement in back pain severity from 7.1 ± 1.6 at baseline to 3.6 ± 2.9 at 24 months was 43% (p< 0.001). Approximately 64% (14 of 22) of participants achieved both the MCID and SCB in back pain at 24 months, while nearly 55% (12 of 22) reported a 24-month back pain severity score of ≤ 3. The corresponding average decrease in ODI values was 53% (p< 0.001) with 73% (16 of 22) of participants achieving the MCID. At baseline approximately 82% (23 of 28) of participants reported severe or crippled back impairment compared to 18% (4 of 22) at 24 months (p< 0.001). There was no association between modified Pfirrmann grade, number of levels treated or Modic changes and any outcome (range: p=0.12 to 0.43).Conclusion: This study provides evidence of clinically significant pain relief and functional improvement through 24 months of follow up after a single allogeneic NP supplementation procedure in patients with lumbar discogenic pain.Keywords: nucleus pulposus, allograft, discogenic, back pain, intradiscal, degenerative disc disease